0568 Objective Improvement in Sleep Depth and Quality Following Initiation of Continuous Positive Airway Pressure for Obstructive Sleep Apnea. (27th April 2018) - Penner, C G; Williams, M; Ryan, R; Gerardy, B
Abstract: Introduction: Treatment of OSA has long been known to improve daytime sleepiness and other indices of daytime functioning (ESS, FOSQ 10/30, SAQLI). Demonstrating objective improvement of sleep depth and quality has remained elusive. The Odds Ratio Product (ORP) has recently been described as a method of objectively measuring sleep depth and quality using the relationships of the powers of different EEG frequencies in a single understandable index. The scale ranges from 0 - 2.5 with values of zero only occurring during sleep and a value of 2.5 only occurring during wakefulness. A value of 1.25 predicts an equal probability of being awake or asleep. The current investigation seeks to establish how much the ORP changes with the introduction of CPAP therapy. Methods: Forty-one adults (23 males/18 females) with OSA or UARS completed the study with a mean AHI of 33.2 ± 28.2, age 48.4 ± 11.0, BMI 35.1 ± 6.2, FOSQ 10 14.8 ± 3.2 and ESS 10.4 ± 5.0. Home sleep studies were done including EEG (Prodigy). A follow-up EEG study was done on CPAP three weeks later. ORP was calculated for all sleep stages (sleep depth) and for all stages after sleep onset (ASO-sleep quality). Results: Mean ORP (sleep) prior to CPAP was 0.71 ± 0.24 vs 0.60±.24 during therapy (p=0.047). Mean ORP (ASO) prior to CPAP was 0.85 ± 0.29 vs 0.71 ± 0.28 during therapy (p=0.028). In 28, ORP decreased on therapy and in 13 increased. Recent data has demonstrated that ORP on consecutive nights isn't systematically different. Arousal/awakening index (AI) prior to therapy was 27.3 ± 14.7 vs 17.5 ± 5 during therapy (p=0.0002). ORP9 (an index of arousability) decreased from 0.95 ± 0.26 to 0.87 ± 0.29 (p>0.05). Multiple linear regression analysis revealed a model with major factors being ∆ORP9 and ∆AI (R 2 =0.779). There was no correlation between ∆FOSQ10 or ∆ESS and ∆ORP. Conclusion: The ORP decreases with CPAP therapy in most patients and provides a simple objective measure of improvement of sleep depth and quality. Support (If Any): Financial and in-kind support was provided Cerebra Health Inc and RANA Respiratory Care Group.